2010
DOI: 10.1074/jbc.m109.055129
|View full text |Cite
|
Sign up to set email alerts
|

The Cleavage of Semaphorin 3C Induced by ADAMTS1 Promotes Cell Migration

Abstract: Metastasis is a sequential process that allows cells to move from the primary tumor and grow elsewhere. Because of their ability to cleave a variety of extracellular signaling and adhesion molecules, metalloproteases have been long considered key components of the metastatic program. However, the function of certain metalloproteases, such as ADAMTS1, is not clear and seems to depend on the cellular environment and/or the stage of tumor progression. To characterize the function of ADAMTS1, we performed two alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 50 publications
5
86
0
Order By: Relevance
“…61,116 Like the other class-3 semaphorins, sema3C too is cleaved in conserved sites by furin like pro-protein convertases as well as by ADAMTS1. 170 The major cleavage product generated by furin like pro-protein convertases (p65-Sema3C) is inactive as an inducers of cell contraction but is still able to support survival of tumor cells in cell culture 61 suggesting that it may perhaps contribute to tumor progression when generated in the tumor microenvironment which is usually enriched with these furins. 171 Likewise, the sema3C cleavage products generated by cleavage with ADAMTS1 promotes the migration of breast cancer cells.…”
Section: Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%
“…61,116 Like the other class-3 semaphorins, sema3C too is cleaved in conserved sites by furin like pro-protein convertases as well as by ADAMTS1. 170 The major cleavage product generated by furin like pro-protein convertases (p65-Sema3C) is inactive as an inducers of cell contraction but is still able to support survival of tumor cells in cell culture 61 suggesting that it may perhaps contribute to tumor progression when generated in the tumor microenvironment which is usually enriched with these furins. 171 Likewise, the sema3C cleavage products generated by cleavage with ADAMTS1 promotes the migration of breast cancer cells.…”
Section: Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%
“…2A; ref. 34). These observations suggest that sema3C is a heparainbinding protein and that binding to heparin or heparan sulfates may be important to its activity.…”
Section: Generation Of An Active Point Mutated Sema3c (Fr-sema3c) Thamentioning
confidence: 99%
“…It was reported that CD36 has been subjected to positive selection for malaria or some unknown selection pressures (Aitman et al 2000;Omi et al 2002Omi et al , 2003Fry et al 2009). SEMA3C, induced by ADAMTS1, promotes the migration of cancer cells (Esselens et al 2010). The 6p21-22 region, harboring human major histocompatibility complex (MHC), also showed an overrepresentation of African ancestry in this study (although <3 SD) and has been reported under selection in various studies (Garrigan and Hedrick 2003;Tang et al 2007).…”
Section: Natural Selection In African Americansmentioning
confidence: 99%